A good team - Burnell, Heather Ayris (New York : Acorn/Scholastic Inc., 2019)
New friends Unicorn and Yeti are having a little trouble finding something they are both good at; Yeti is good at kicking a ball, Unicorn is not, Unicorn is fast, Yeti is not--so they finally try ice skating, which neither of them has ever done, because they have a chance to be equally good (or bad) at it.
Kirkus Review, May 2019
0.9
K-3
330L
Keywords: Unicorns -- Juvenile fiction; Yeti -- Juvenile fiction; Ability -- Juvenile fiction; Friendship -- Juvenile fiction; Humorous stories; Unicorns -- Fiction; Yeti -- Fiction; Ability -- Fiction; Friendship -- Fiction; Humorous stories; Humorous fiction